Prevalence of hanseniasis cases in the municipality of Votuporanga (SP) in the period 2014 to 2018 (Revista Brasileira Multidisciplinar, 2020)
Leprosy is caused by Hansen's bacillus, which affects the skin and peripheral nervous system. Brazil has a detection rate of 12.2 / 100 thousand inhabitants. The objective of the research was to analyze the cases of leprosy in the municipality of Votuporanga / SP, between 2014 to 2018. Data were collected from Datasus at the end of 2018. Of the 33 cases, 51, 5% were in males and 48, 5% in females, the majority between the ages of 30 and 59 (58%). The mode of entry was the predominance of new cases (76%). Routing was the most commonly used detection mode (52%); the spontaneous demand, 18%, examination of contacts, 18% and others,  12%. As to the clinical form, 34% were virchowiana, 24% dimorphic, 27% tuberculoid and 15% undetermined, thus, the Multibacillary form (58%) and the Paucibacilar form (42%) were highlighted The therapeutic regimen confirms the data already mentioned, with more prevalent MDT / MB / 12 doses (58%). The affected skin lesions and nerves were mostly ignored. The degree of disability was found to be more significant (79%), 15% had disability grade 1 and 6% were already in grade 2. The type of output with the highest percentage was the cure (70%), transfers reached  6%  and 21% don’t appear in the records. The municipality studied did not reach the goal of elimination and presents many contagious forms. It is extremely important to identify and treat cases; and to invest in disability preventions.